Institutional achitectures and behavioural ecologies in the dynamics of financial markets: A preliminary investigation - Giulio Bottazzi; Giovanni Dosi; Igor Rebesco (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2002)
The paper compares the properties of market dynamics, under different trading protocols. At an empirical level, we present some evidence stemming from the comparison between different intra-daily trade regimes within the world largest Stock Exchanges. Such evidence also motivates the investigation of the properties of an agent-based model under three alternatives market mechanisms, namely a Walrasian auction, a batch auction and an 'order-book' double auction. The results highlight the importance of market mechanisms per se, even when holding constant the behavioural characteristics of the agents.
Keywords: 330; Evolutionary Finance; Market Institutions; Agent Based Modelling; Finanzmarkt; Wertpapierhandel; Marktmechanismus; Auktionstheorie